(+1 supra 3 )+(-1 supra 6 )+(-1 supra 4 )+(+3 supra 2 )=
Răspunsuri la întrebare
Răspuns de
0
1/3 - 1/6 -1/4+ 3/2 = 4/12 - 2/12 -3/12 +18/12= 17/12
AnaMaria7b:
Multumesc!
Răspuns de
1
(+1/3)+(-1/6)+(-1/4)+(+3/2)
(((0+1/3)+(0-1/6))+(0-1/4))+(0+3/2)
0*23+3/2=3/2
(((0+1/3)+(0-1/6))+(0-1/4))+3/2
(((0+1/3)+(0-1/6))+-1/4)+3/2
(((0+1/3)+ -1/6)+ -1/4)+3/2
0*3+1/3=1/3
2+ -1/6=1/6
(1/6+ -1/4)+3/2
2+ -1*3/12=-1/12
-1/12+3/2
-1+3*6/12=17/12
17/12=1,41667
(((0+1/3)+(0-1/6))+(0-1/4))+(0+3/2)
0*23+3/2=3/2
(((0+1/3)+(0-1/6))+(0-1/4))+3/2
(((0+1/3)+(0-1/6))+-1/4)+3/2
(((0+1/3)+ -1/6)+ -1/4)+3/2
0*3+1/3=1/3
2+ -1/6=1/6
(1/6+ -1/4)+3/2
2+ -1*3/12=-1/12
-1/12+3/2
-1+3*6/12=17/12
17/12=1,41667
Alte întrebări interesante
Informatică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă